Pengaruh Karakteristik Pemerintah Daerah terhadap Prediksi Financial Distress pada Kabupaten/Kota di Provinsi Sumatera Barat Tahun 2016-2020 - Rahmi, Harma Sri Lidia; Sari, Vita Fitria (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to determine the effect of local government characteristics (Decentralization, Area and Government Complexity) on financial distress in districts/cities in West Sumatra Province from 2016-2020. The data in this study uses secondary data that is processed from local government financial reports (LKPD) from the Supreme Audit Agency of West Sumatra Province and the area and number of Regional Apparatus Work Units (SKPD) from the Central Statistics Agency of West Sumatra Province. The sampling technique in this study used the total sampling method with a sample of 19 districts/cities with a period of 5 years. Data analysis using multiple regression analysis. The results of this study indicate that there is one variable characteristic of local government, namely the area that has a significant influence on financial distress in a positive direction, for other variables the characteristics of local governments have an insignificant relationship where the direction of the negative relationship consists of the number of SKPD, and for the direction of the relationship positive consists of decentralization.